Cultural Transmission through Auspicious Symbols in Lang Shining’s Flora Paintings - Butrach, Pancheewa (Silpa Bhirasri (Journal of fine arts), 2023)
This article aims to study the cultural transmission through auspicious symbols in the flora painting collections of Lang Shining (郎世宁), an Italian artist who served as a court painter during the Golden Era of the Qing dynasty, from the reign of Kangxi, Yongzheng to Qianlong emperor. This qualitative research aims to study documentary research, e.g., academic papers and textbooks, including field notes. The fieldwork observes and collects Lang’s Paintings information in the National Museum (Taipei). Afterward, the researcher organizes paintings by auspicious symbol themes to make the final comparative analysis between auspicious symbol themes related to Lang’s paintings. The painting types, concepts, and auspicious beliefs in traditional Chinese paintings are studied by two flora paintings and a 16-piece "Immortal Blossoms of an Eternal Spring" set. The study revealed the auspicious belief grouping through Lang’s flora painting as following concepts: 1) Heroic character with gracefulness and nobility; 2) Longavity or immortality; 3) Wealth; 4) Fertility or a perfect family; 5) Happiness or a prosperous life. Lang’s flora paintings represented his skill in oil painting techniques with fine-brush style. This flower collection not only maintained Chinese stylistic brushwork incorporated with Western art of realism and composition but also abounded with auspicious signs of Chinese culture.